Improving power quality in micro-grid - Kyaw, Min Thein (2015)
Unified Power Quality Conditioner (UPQC) has been a favourable candidate for high performance power conditioning devices due to its feasibility and ability to mitigate all power quality problems. It will be very useful in the future micro-grid systems where power quality issues will be more pervasive and severe due to greater use of power electronics devices and non-linear loads. In this project, among various types of UPQC, a three-phase three-wire (3P3W) topology with power angle control (PAC) method was selected to analyse thoroughly. The theories of PAC technique were studied and implemented with Simulink blocks .Various power quality problems such as voltage sag, voltage swell, voltage harmonic distortions, high power factor issue and current distortions were applied to the system in order to test the effectiveness of PAC method. The simulation results reveal that the PAC approach is able to solve the aforementioned power quality issues effectively. Moreover, as the PAC method can be further categorized into fixed PAC method and variable PAC method according to their power angle determination techniques, both methods were simulated in order to find out their main differences for future development.